Groundwater Quality Assessment for Drinking Purpose Based on Physicochemical Analysis in Teluk Nilap Area, Rokan Hilir, Riau, Indonesia. - Arief Yandra Putra; Fitri Mairizki (UIR PRESS, 2020)
Groundwater is water resource that widely used for domestic purposes, including for drinking. However, the industrial and population growth causes the quality and quantity of groundwater to decline. In this case, the quality of drinking water in Indonesia must meet the requirements according to Health Minister Regulation No.492/MENKES/PER/IV/2010. This study aims are to determine the quality of groundwater in the research area based on physicochemical parameters and its evaluation for drinking water. Groundwater samples were taken from dug wells in Teluk Nilap area, Rokan Hilir, Riau. Groundwater samples have temperature average 30oC, TDS average 312,5 mg/L and pH average 5,6. Groundwater contain sulfate and nitrate with average value 48,8 mg/L and 11,86 mg/L, respectively. Groundwater water also have iron and lead metal above the permitted standard with average value 2,57 mg/L and 0,022 mg/L. Groundwater in the study is not recommended as drinking water.